Young leaf protection from cadmium accumulation and regulation of nitrilotriacetic acid in tall fescue (Festuca arundinacea) and Kentucky bluegrass (Poa pratensis). (December 2018) - Fei, Ling; Xu, PeiXian; Dong, Qin; Mo, Qi; Wang, ZhaoLong
Abstract: Phytoextraction efficiency of cadmium (Cd) contaminated soil mainly depended upon the mechanism of plants in absorption, translocation, distribution, and detoxification of Cd. A pot experiment was designed to investigate Cd distribution and accumulation among the different leaves of tall fescue ( Festuca arundinacea ) and Kentucky bluegrass ( Poa pratensis ) and its regulation by Nitrilotriacetic acid (NTA), a biodegradable chelating agent. The results showed that Cd concentrations in the senescent and dead leaves were 3.2 and 5.3 fold of that in the emerging leaves of tall fescue, and 19.3 and 25.1 fold of that in the emerging leaves of Kentucky bluegrass, respectively. The lower Cd concentrations were maintained in the emerging and mature leaves to avoid Cd toxicity. In the emerging and mature leaves, Cd was mainly accumulated in the vascular bundles and epidermis. No Cd dithizonate color was observed in the mesophyll tissues of Kentucky bluegrass and only minor Cd was observed in the mesophyll tissues of tall fescue. In the senescent leaves, Cd dithizonate complexes were located in the protoplasts and cell walls of all leaf tissues. NTA greatly promoted Cd translocation and distribution to the senescent and dead leaves of tall fescue, but no significant effect was observed in Kentucky bluegrass. Our results indicate that a young leaf protection mechanism might be involved in their Cd hypertolerance. The Cd preferential accumulation could lead a novel phytoextraction strategy by the continuously harvesting the senescent and dead leaves of tall fescue and Kentucky bluegrass. Highlights: The majority of Cd was accumulated in the senescent and dead leaves. Young leaves was protected by less Cd accumulation and less Cd distributed in mesophyll tissues. Nitrilotriacetic acid promoted the young leaf protection in tall fescue, but not in Kentucky bluegrass.